2001
DOI: 10.1680/ijpmg.2001.010201
|View full text |Cite
|
Sign up to set email alerts
|

Development and performance of an active type shear box in a centrifuge

Abstract: An active type shear box in a geotechnical centrifuge has been newly developed for investigating behaviour of structures subjected to large soil movement. This shear box was designed focusing on deformation of a pile due to lateral movement of soil during earthquake under quasi-static conditions, neglecting inertial effects of soil and pile. The apparatus consists of a laminar box and actuators. With the actuators mounted beside the laminar box, the deformation of the laminar box can be controlled and any grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…Tateishi (1995) suggested by comparative results of numerical analysis that a static FE analysis with this type of the loading condition, in which the ground is modelled by solid elements, cannot create appropriate earthquake-induced shear strain in the ground, i.e., the shear strain varies with the distance from the boundaries on which the displacement is given. The previous experimental studies with the active type shear box reported the similar results; Takahashi et al (2001) used the original shear box and reported 70-80z of the input nominal shear strain under the conditions of 325 mm deep Toyoura sand of relative density of 80z under 25 g. Yamada et al (2002) also used the original shear box and reported 70z under the conditions of 300 mm deep Toyoura sand of relative density of 90z under 50 g. Although the test conditions and material properties are diŠerent in these tests, the general trend is similar to the previous observations. However, in both the tests, even though the magnitude of the horizontal displacement was smaller than that at the side boundaries, the horizontal displacement prole at the center of the box was similar to that at the side boundaries.…”
Section: Model and Test Descriptionssupporting
confidence: 74%
See 1 more Smart Citation
“…Tateishi (1995) suggested by comparative results of numerical analysis that a static FE analysis with this type of the loading condition, in which the ground is modelled by solid elements, cannot create appropriate earthquake-induced shear strain in the ground, i.e., the shear strain varies with the distance from the boundaries on which the displacement is given. The previous experimental studies with the active type shear box reported the similar results; Takahashi et al (2001) used the original shear box and reported 70-80z of the input nominal shear strain under the conditions of 325 mm deep Toyoura sand of relative density of 80z under 25 g. Yamada et al (2002) also used the original shear box and reported 70z under the conditions of 300 mm deep Toyoura sand of relative density of 90z under 50 g. Although the test conditions and material properties are diŠerent in these tests, the general trend is similar to the previous observations. However, in both the tests, even though the magnitude of the horizontal displacement was smaller than that at the side boundaries, the horizontal displacement prole at the center of the box was similar to that at the side boundaries.…”
Section: Model and Test Descriptionssupporting
confidence: 74%
“…The geotechnical group at the Tokyo Institute of Technology developed the active type shear box apparatus for centrifuge model tests (Takahashi et al, 2001). The original shear box was modiˆed to increase the depth of the shear box to accommodate a larger cover depth, since a tunnel cover (C)/diameter (D) ratio is an important factor for the stress condition around the tunnel (Takemura et al, 2006).…”
Section: Model and Test Descriptionsmentioning
confidence: 99%
“…The boundary effects in a large shear stack are smaller than in table-top shear devices and the volume of soil situated in the central part of the container reproduces better the free field conditions for a given wavelength. It is also known that the design of a shear stack can be tuned to operate over wide strain ranges with granular materials of different stiffness value [19]. This, in particular, makes the shear stack useful for studying the large-strain dynamic moduli under seismic excitation.…”
Section: Introductionmentioning
confidence: 99%